Proceedings of the Thirtieth Annual ACM-SIAM Symposium on Discrete Algorithms 2019
DOI: 10.1137/1.9781611975482.31
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Tensors and Opportunistic Boolean Matrix Multiplication

Abstract: We introduce probabilistic extensions of classical deterministic measures of algebraic complexity of a tensor, such as the rank and the border rank. We show that these probabilistic extensions satisfy various natural and algorithmically serendipitous properties, such as submultiplicativity under taking of Kronecker products. Furthermore, the probabilistic extensions enable improvements over their deterministic counterparts for specific tensors of interest, starting from the tensor 2, 2, 2 that represents 2 × 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Cohn and Umans [17] introduced the notion of the support rank of tensors, and showed that upper bounds on the support rank of matrix multiplication tensors can be used to design faster Boolean matrix multiplication algorithms. Recently, Karppa and Kaski [23] used "probabilistic tensors" as another way to design Boolean matrix multiplication algorithms.…”
Section: Other Related Workmentioning
confidence: 99%
“…Cohn and Umans [17] introduced the notion of the support rank of tensors, and showed that upper bounds on the support rank of matrix multiplication tensors can be used to design faster Boolean matrix multiplication algorithms. Recently, Karppa and Kaski [23] used "probabilistic tensors" as another way to design Boolean matrix multiplication algorithms.…”
Section: Other Related Workmentioning
confidence: 99%
“…There is one critical difference between our analysis and that of [11]. In [11], the only relevant factor was the gross count of the number of terms computed by the pseudo-multiplication algorithm.…”
Section: Introductionmentioning
confidence: 98%
“…It seems difficult to make progress on better practical algorithms for matrix multiplication. In [11], Karppa & Kaski proposed a novel type of algorithm to break this impasse. Instead of reducing BMM directly to matrix multiplication, one reduces to to a randomized "broken" or "opportunistic" form of matrix multiplication.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations